Pengaruh Faktor-Faktor Psikologi Terhadap Keputusan Investasi Saham Syariah Di Yogyakarta - Sarni Handayani Puspita Sari (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze several psychological factors that have an influence on investors' investment decisions in the Province of the Special Region of Yogyakarta. The number of samples in this study were 180 respondents. The method for determining the sample is the convenience sampling method where data collection is through a questionnaire. Data analysis using Structural Equation Modeling (SEM) with Partial Least Square using SmartPLS software version 3.0. The data analysis methods in this study are the convergent validity test, the outer model, the reliability test (composite reliability and cronbach's alpha) and the average variance extracted (AVE) value test, the discriminant validity test, see cross loading, compare the AVE root values, test the inner model , R square analysis, Effect size (f2), Predictive relevance (Q2), goodness of fit index (GOF). The results of the first hypothesis test show that there is an influence between optimism on investment decision making. The results of the second hypothesis testing show that there is no influence between herding on investment decision making. This shows that an investor often imitates information from other people. The results of the third hypothesis test show that overconfidence in investment decisions has a significant and positive relationship. This means that the higher a person behaves overconfidence, the more confident they will be in their experience and abilities. The results of the fourth hypothesis test show that there is a positive and significant relationship between conservatism on investment decision making. The results of the fifth hypothesis test show that there is no effect of Availability Bias on investment decision making.